2023
DOI: 10.1038/s41598-023-32677-3
|View full text |Cite
|
Sign up to set email alerts
|

The combination of rolipram and cilostamide improved the developmental competence of cloned porcine embryos

Abstract: In vitro maturation of porcine oocytes is characterized by asynchronous cytoplasmic and nuclear maturation, leading to less competent oocytes supporting embryo development. The purpose of this study was to evaluate the combined effect of rolipram and cilostamide as cyclic Adenine monophosphate (cAMP) modulators to find the maximum cAMP levels that temporarily arrest meiosis. We determined the optimal time to maintain functional gap junction communication during pre-in vitro maturation to be four hours. Oocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 109 publications
0
1
0
Order By: Relevance
“…In this research, Parthenogenetic embryos were employed. Because parthenogenesis technology is mature, the embryo development state is good, a lot of embryos with diploid features are easy to obtain, and there is no bias of paternal contribution; porcine parthenogenetic embryos were used as an excellent model to detect early embryo development [36,37]. We found that exposure to 100 µM BDE-47 significantly decreased the blastocyst rate.…”
Section: Discussionmentioning
confidence: 85%
“…In this research, Parthenogenetic embryos were employed. Because parthenogenesis technology is mature, the embryo development state is good, a lot of embryos with diploid features are easy to obtain, and there is no bias of paternal contribution; porcine parthenogenetic embryos were used as an excellent model to detect early embryo development [36,37]. We found that exposure to 100 µM BDE-47 significantly decreased the blastocyst rate.…”
Section: Discussionmentioning
confidence: 85%